Bandgap-tunable black phosphorus quantum dots: visible-light-active photocatalysts. Issue 8 (10th January 2018) - Yuan, Yong-Jun; Yang, Shuhui; Wang, Pei; Yang, Yan; Li, Zijian; Chen, Daqin; Yu, Zhen-Tao; Zou, Zhi-Gang
Abstract : Bandgap-tunable black phosphorus quantum dots were prepared by a liquid exfoliation method for the photocatalytic degradation of rhodamine B. Abstract : Bandgap-tunable black phosphorus quantum dots prepared by a liquid exfoliation method in a mixture solvent of N -methylpyrrolidone and oleic acid can act as efficient photocatalysts for the degradation of rhodamine B. This is the first report on solely black phosphorus capable of destroying organic pollutants under visible light irradiation.